Nutrition Intake, Physical Activity, and Sleep Quality in the Month of Fast During Covid-19 Pandemic - Widya Hary Cahyati; Natalia Desy Putriningtyas; Wara Dyah Pita Rengga; Suharyo Suharyo (Jurnal Kesehatan Masyarakat, 2023)
Central Java is one of the provinces with the highest number of positive Covid-19 cases in Indonesia, with 46,903 positive infected cases, with a death rate of 2,110 people (4.49%).  During the COVID-19 pandemic, community activities decrease, especially during the fasting month.  Their diet has also changed.  This study aimed to describe and analyse the relationship between nutritional intake and physical activity on people's sleep quality during the fasting month during the COVID-19 pandemic.  The benefit of this research is to provide information on factors related to people's sleep quality, so as to improve public health. The novelty of this research is on aspects of physical activity, and people's sleep quality during the fasting month during the covid-19 pandemic. This research method is observational using a cross-sectional approach. The research was conducted during the fasting month (Ramadan 2021) to find out the nutritional intake, physical activity, and quality of people's sleep while fasting amid the COVID-19 pandemic. This study was attended by 520 respondents who were willing to fill out a questionnaire distributed via Googleform. Respondents in this study were limited to people who live in Central Java. The selection of respondents using the cluster sampling technique and then the snowball method.  The questionnaires were the Pittsburgh Sleep Quality Index (PSQI), IPAQ and DQI.  The results showed no relationship between physical activity and slept quality during the fasting month (p : 0.402).  There is a relationship between food consumption, sleep quality (p: 0.0001), and physical activity (0.007) during the fasting month.